INFLUENCE OF COMPETITIVE STRATEGIES ON SMALL AND MICRO ENTERPRISES’ PERFORMANCE: SURVEY OF ELECTRONICS SHOPS IN MACHAKOS TOWN AND ENVIRONS - NJOROGE, REUBEN KIMANI (Machakos University Press, 2021)
Small and Microenterprise (SME) is a vital economic sector in Kenyan since it employs about 85% of the total Kenyan workforce.Competitive strategies practiced by SMEs determine their growth and longtime survival.This study intended to investigate the influence of various generic competitive strategies on performance of SMEs in Machakos Town and its environs.The study was guided by four objectives namely;influence of cost leadership strategy,influence of differentiation strategy,influence of focus strategy and influence of hybrid strategy on performance of Small and Micro enterprises (SMEs) in Machakos town and its environs.Semi-structured questionnaires were administered by the researcher on the respondents to collect data.The study employed census sampling technique on a population of 40 registered electronics retail firms in Machakos town.The target respondents for this study were either owners or managers of licensed electronics retail firms operating in Machakos Town. Reliability and validity of the research instrument was tested by conducting a pilot test on 6 respondents randomly selected from the target population.The collected data was analyzed and findings presented using tables and bar charts to help make comparison of data,identify relationship between practice of generic competitive strategies and SMEs performance.Multiple regression analysis was used to establish the nature and magnitude of the influence of practice of cost leadership strategy,differentiation strategy,focus strategy and hybrid strategy on SMEs performance in Machakos town.The R Square value for this study was 0.705; this range between 0 and 1.Analytically,this shows that 70.5% of variations in the dependent variable can be explained by the independent variables.This means 70.5% of variations in Performance of Small and Micro Enterprises (SMEs) can be explained by cost leadership strategy,differentiation strategy,hybrid strategy and focus strategy,while the remaining 29.5 % is associated with factors that are not within the scope of this study.From the findings in the regression analysis, if the factors Cost Leadership Strategy, Differentiation Strategy, Hybrid Strategy, Focus Strategy) were held constant Performance of Small and Micro Enterprises (SMEs) would be at 0.971.A unit increase in each independent variables would lead to an increase in Performance of Small and Micro Enterprises (SMEs) by value of its beta coefficient where beta coefficient for Differentiation, Focus,Hybrid and Cost Leadership Strategies are 0.184,0.355,0.764 and 0.306 respectively.The study revealed that SMEs practicing focus strategies concentrate on particular niche markets, understand unique customers needs then develop uniquely low-cost or well-differentiated products for the market.The study findings concluded that cost leaders tend to keep their costs low by minimizing on advertising, market research,and product development costs.The study concluded that differentiation strategy is best exploited by SMEs offering specialized services like repair of electronic household goods and mobile phones.The regression analysis explains only 70.5% of relationship between performance of SMEs in Machakos Town and cost leadership,differentiation,focus and hybrid strategies.This implies that 29.5% of variations on performance of SMEs in Machakos town and its environs are linked to other factors outside this study.More studies therefore need to be carried out to establish these additional factors and how they impact on performance of SMEs in Machakos Town.